Entrepreneurship Learning and Entrepreneurial Motivation Kemenkes Padang Poltekkes Students - Mahaza, Mahaza; Marza, R firwandri; Sartika, Wiwi; Husna, Riyana (Universitas Aisyah Pringsewu, 2024)
Entrepreneurship courses have been given to students in all departments at the Ministry of Health's Poltekkes. However, there is no data that shows whether there are students who are entrepreneurs and have never been evaluated for learning, so for the development of this course and how students motivate them to become entrepreneurs after learning entrepreneurship courses, it is necessary to evaluate learning and how student entrepreneurship motivation is become an entrepreneur after studying entrepreneurship courses, so for that it is necessary to evaluate learning and how the entrepreneurial motivation of students of this padang health polytechnic is. The purpose of evaluating the learning process of the Entrepreneurship Course and curating the motivation of the ministry of health police students in entrepreneurship. This study falls within the realm of descriptive research, focusing on the exploration of independent variables, whether singular or multiple, without involving comparisons or establishing connections between these variables. The research targets students who are currently enrolled in Entrepreneurship Courses at the Polytechnic College of the Ministry of Health, Republic of Indonesia, situated in Padang. Specifically, the emphasis is placed on students who participated in Entrepreneurship Courses during the 2018/2019 Academic Year. Inclusion criteria encompass compliance with attendance, possession of boundary books and course materials, and overall alignment with the designated curriculum. Additionally, students are expected to have attained a course grade exceeding 95% (Grade A) and not less than 5% (Grade B). The study also takes into account various variables, including students' motivation for entrepreneurship, involvement in a Special Web Tracer Study conducted by the Polytechnic College of the Ministry of Health in Padang for Graduates, and the subsequent dissemination of both tracer study results and findings related to Graduate Entrepreneurship. (Need To Train Wierhadap Lecturers on Online Curriculum, Continue this Research to The Variable-Variavel Tracer Study which is needed by each Study Program